Legal Barriers to Implementing Recommendations for Universal, Routine Prenatal HIV Testing - Wolf, Leslie E.; Lo, Bernard; Gostin, Lawrence O. (The Journal of law, medicine & ethics, 2004)
Administraation of antiretroviral therapy to women during pregnancy, labor and delivery, and to infants postnatally can dramatidy reduce mother-to- child HIV transmission (MTCT). However, pregnant women need to know that they are HIV-infected to take advantage of antiretroviral therapy, and many women do not know their HIV status. One-half of HIV-infected infants in the United States were bornto women who had not been tested for HIV or for whom the time of testing was not known. Although fewer than 400infants are infected perinatally in the United States each year, that number could be reduced even further through policies aimed at HIV testing during pregnancy. The reasons toadopt such a policy are strong: the pathophysiology of perinatal transmission is clear, prophylaxis is effective and safe, and the intended beneficiaries of the intervention - babies - cannot protect themselves.